Isn't is the sum of differences ?

Calculus Level 3

Find the value of n n for which r = 1 n r 4 + r 2 + 1 r 4 + r = 675 26 \displaystyle \sum_{r=1}^n \dfrac{r^4+r^2+1}{r^4+r}=\dfrac{675}{26}


You can try my other Sequences And Series problems by clicking here : Part II and here : Part I.


The answer is 25.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Tasmeem Reza
Feb 12, 2015

Notice that, r 4 + r 2 + 1 = r 4 + 2 r 2 + 1 r 2 = ( r 2 + 1 ) 2 r 2 = ( r 2 + r + 1 ) ( r 2 r + 1 ) r^{4}+r^{2}+1 = r^{4}+2r^{2}+1 - r^{2} = (r^{2}+1)^{2} - r^{2} \\ = (r^{2}+r+1)(r^{2}-r+1) Again, r 4 + r = r ( r 3 + 1 ) = r ( r + 1 ) ( r 2 r + 1 ) r^{4}+r = r(r^{3}+1) = r(r+1)(r^{2}-r+1)

Thus we get, r = 1 n r 4 + r 2 + 1 r 4 + r = r = 1 n ( r 2 + r + 1 ) ( r 2 r + 1 ) r ( r + 1 ) ( r 2 r + 1 ) \sum_{r=1}^{n} \frac{r^{4}+r^{2}+1}{r^{4}+r} = \sum_{r=1}^{n} \frac{(r^{2}+r+1)(r^{2}-r+1)}{r(r+1)(r^{2}-r+1)} = r = 1 n ( r 2 + r + 1 ) r ( r + 1 ) = r = 1 n ( 1 + 1 r ( r + 1 ) ) = \sum_{r=1}^{n} \frac{(r^{2}+r+1)}{r(r+1)} = \sum_{r=1}^{n}\left ( 1+\frac{1}{r(r+1)} \right ) = r = 1 n 1 + r = 1 n 1 r ( r + 1 ) = n + r = 1 n ( 1 r 1 r + 1 ) = \sum_{r=1}^{n} 1 + \sum_{r=1}^{n} \frac{1}{r(r+1)} = n + \sum_{r=1}^{n}\left ( \frac{1}{r} - \frac{1}{r+1} \right )

Now, r = 1 n ( 1 r 1 r + 1 ) = ( 1 1 1 2 ) + ( 1 2 1 3 ) + . . . + ( 1 n 1 n + 1 ) \sum_{r=1}^{n}\left ( \frac{1}{r} - \frac{1}{r+1} \right ) = \left ( \frac{1}{1} - \frac{1}{2} \right )+\left ( \frac{1}{2} - \frac{1}{3} \right ) + ... + \left ( \frac{1}{n} - \frac{1}{n+1} \right ) = 1 1 n + 1 [ Telescoping ] =1-\frac{1}{n+1} \left [ \textrm{Telescoping} \right ]

n + r = 1 n ( 1 r 1 r + 1 ) = n + ( 1 1 n + 1 ) = 675 26 = 26 1 26 \therefore n + \sum_{r=1}^{n}\left ( \frac{1}{r} - \frac{1}{r+1} \right ) = n + \left ( 1-\frac{1}{n+1} \right ) = \frac{675}{26} = 26 - \frac{1}{26} n 1 n + 1 = 25 1 26 \Rightarrow n-\frac{1}{n+1} = 25 - \frac{1}{26} \therefore Its easy to see that n = 25 n = \boxed{25} satisfies the equation.

xcellent !

Mayank Holmes - 6 years, 4 months ago

Log in to reply

¨ \huge\ddot\smile

tasmeem reza - 6 years, 4 months ago

especially the last part ! it seemed too good !

Mayank Holmes - 6 years, 4 months ago

The last part is really astounding. Beside, using the quadratic formula is also true, right?

Figel Ilham - 6 years, 3 months ago
Brock Brown
Feb 17, 2015

Python:

 1
 2
 3
 4
 5
 6
 7
 8
 9
10
11
12
from fractions import Fraction as frac
memo = {1:frac(3,2)}
def f(n):
    if n in memo:
        return memo[n]
    memo[n] = f(n-1)+frac(n**4+n**2+1,n**4+n)
    return memo[n]
n = 1
goal = frac(675,26)
while f(n) != goal:
    n += 1
print "Answer:", n

How to use that?

. . - 4 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...